2012
DOI: 10.1182/blood-2012-01-407593
|View full text |Cite
|
Sign up to set email alerts
|

BMP9 and BMP10 are critical for postnatal retinal vascular remodeling

Abstract: ALK1 is a type I receptor of the TGF-β family that is involved in angiogenesis. Circulating BMP9 was identified as a specific ligand for ALK1 inducing vascular quiescence. In this work, we found that blocking BMP9 with a neutralizing antibody in newborn mice significantly increased retinal vascular density. Surprisingly, Bmp9-KO mice did not show any defect in retinal vascularization. However, injection of the extracellular domain of ALK1 impaired retinal vascularization in Bmp9-KO mice, implicating another li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
289
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 215 publications
(308 citation statements)
references
References 38 publications
15
289
0
1
Order By: Relevance
“…We also found that BMP9 and BMP10 strongly induced the mRNA expression of several transcription factors (SNAI1, SNAI2, ZEB2, TWIST1, and FOXC2) known to be important in the initiation of EMT or endMT (14). In accordance, it has already been described that BMP9 and BMP10 transiently induce the expression of HEY1, HEY2, and HES1 (8,24), which are transcription factors of the Notch signaling pathway also known to be involved in EMT (14). Taken together, these data allow us to propose that, in Bmp9-KO pups injected with anti-BMP10 antibody (P1 and P3), ECs fail to go through a transition into a mesenchymal-like phenotype, and this defect of remodeling leads to loose cell interactions that will result in the reopening of the DA.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…We also found that BMP9 and BMP10 strongly induced the mRNA expression of several transcription factors (SNAI1, SNAI2, ZEB2, TWIST1, and FOXC2) known to be important in the initiation of EMT or endMT (14). In accordance, it has already been described that BMP9 and BMP10 transiently induce the expression of HEY1, HEY2, and HES1 (8,24), which are transcription factors of the Notch signaling pathway also known to be involved in EMT (14). Taken together, these data allow us to propose that, in Bmp9-KO pups injected with anti-BMP10 antibody (P1 and P3), ECs fail to go through a transition into a mesenchymal-like phenotype, and this defect of remodeling leads to loose cell interactions that will result in the reopening of the DA.…”
Section: Discussionsupporting
confidence: 72%
“…In 2007, it was demonstrated that BMP9 and BMP10 bind with high affinity to the endothelial-specific receptor activin receptor-like kinase 1 (ALK1), a type 1 receptor of the TGFβ family (6) whose mutations are involved in vascular diseases (5). Both BMP9 and BMP10 are present in blood, and their circulating levels are particularly elevated in mice around birth (7,8), suggesting that they could play a role in pre-and postnatal development. In the present work, we addressed whether BMP9 and BMP10 could be involved in DA closure.…”
mentioning
confidence: 99%
“…1) may have been caused by differences in the method used to inhibit ALK-1 signaling. Furthermore, this variance may also have been caused by the contribution of BMP-10, which is another physiological ligand of ALK-1 (29). Although Bmp10-deficient mice exhibit severe defects in cardiac tissues, no phenotypes in vascular systems have been described in Bmp10-deficient mice (27), suggesting that the physiological roles of BMP-10 may be limited to the cardiac development.…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence have suggested that BMP-9 and BMP-10 are the physiological ligands for ALK-1 (27)(28)(29). To examine whether the loss of Bmp9 expression exhibits phenotypes similar to those observed in Alk1-depleted mice, we analyzed the structure of LVs in Bmp9 KO mice.…”
Section: Deletion Of Bmp9 Expression Induced Dilation Of the Lymphaticmentioning
confidence: 99%
See 1 more Smart Citation